Bilateral superior cerebellar artery pure arterial malformation masquerading as aneurysms - Hazem Shoirah, MD; Rafique Haynes, MD; Gesille Fiallo, PA (Radiology Case Reports)
Pure artery malformation (PAM) is defined as a coil-like dilated and or overlapping appearance of arterial vessels in the absence of a venous component [1]. We report the case of a young adult who presented with a headache and was found to have a pure artery malformation of the bilateral superior cerebellar arteries (SCA), initially masquerading as a basilar tip aneurysm. Given the uncertainty in the diagnosis on noninvasive neuroimaging, a digital subtraction angiography (DSA) was pursued, confirming the diagnosis of PAM. The long-term significance of PAMs remains unknown, but diligent initial evaluation is necessary to rule out alternative diagnoses, especially in an acute setting.